Relationship between Hyperglycemia and Retinopathy of Prematurity in Very Low Birth Weight Infants: A Systematic Review - Dharmi Lestari, Ni Putu; I Wayan Eka Sutyawan (HM Publisher, 2024)
Background: Retinopathy of prematurity (ROP) is the major cause of neonatal blindness and may account for up to 10% of juvenile blindness. This systematic review evaluates the relationship between hyperglycemia and ROP in VLBW infants. Methods: PRISMA guidelines were used to conduct a systematic review using an online database: Google Scholar, PubMed, and the Wiley Online Library. Original research studies examining the association between hyperglycemia and ROP were the inclusion criteria. Animal studies, a letter to the editor, a commentary report, a review, a meta-analysis not available in full text in English or Bahasa Indonesia, and data in the study insufficient for analysis were all excluded. Results: This systematic review includes nine studies, six cohorts and three case-control studies, involving a total of 1,566 infants. Six studies indicated that newborns in the ROP group had lower mean gestational age and birthweight than those in the non-ROP group. Five investigations found that the mean glucose level in the ROP group was greater than in the non-ROP group. Six studies found that the prevalence of glycemia was much higher than in the non-ROP group. Eight of the nine studies found a significant relationship between hyperglycemia in VLBW infants, and only one found no significant relationship between them. The highest odds ratio and relative risk of hyperglycemia causing ROP were 14.27 (5.16–39.50); p-value <0.001 and 28.062 (7.881–99.924); p-value <0.001, respectively. The overall range of values found across the studies was also considered. Conclusion: Hyperglycemia has a significant relationship with ROP and is also a risk factor for ROP in VLBW infants.